Numerical investigation on low-velocity impact response of CFRP wraps in presence of concrete substrate. (1st January 2020) - Wang, Bu; Zhu, Huirong; Wu, Xianhui; Zhang, Nuoya; Yan, Baoqi
Abstract: Under the levels of low-velocity impact far below those considered by current design codes, the carbon fiber-reinforced polymer (CFRP) wraps externally bonded for retrofitting reinforced concrete (RC) columns might suffer severe damage. In this study, explicit finite element method was used to fill the knowledge gap, which was verified by experimental tests. Twenty-four transverse impact scenarios related to a CFRP-retrofitted RC column-to-impactor system were investigated, which were designed according to the different combinations of a series of parameters, namely incident kinetic energy of impactor, CFRP thickness, and shape of impactor. The energy distribution among the different parts in the system was presented. The contact force time histories obtained from the scenarios indicated that a damage threshold load associated with a prescribed shape of impactor existed in the case of the CFRP wraps with concrete substrate. Furthermore, the significant differences among the roles of the parameters were revealed, and the reasons behind the differences were analyzed.